Formation and development of the region’s export potential - Abylkasimova, Zh.; Kalinkin, A.; Akisheva, D.; Orynbekova, G.; Alibayeva, M. (Journal of Economic Research & Business Administration, 2021)
In modern conditions in the national economy, special attention is paid to foreign economic activity, in particular exports. This is reflected in the systematic and large-scale support from the state in the field of exports in order to overcome barriers to access to foreign markets. In Kazakhstan, state support for exports is an important part of foreign economic policy. To promote export products and increase export volumes in modern conditions, the country uses a number of measures and tools, ranging from creating a favorable climate for exporters to stimulating measures for the development of high-tech export production. Thanks to the development of export potential, the state increases financial flows and thus tries to maintain the sustainable development of the country’s economy. At the same time, despite the support from the state, the share of raw materials in the structure of Kazakhstan’s exports exceeds the share of processed goods. The downward trend is observed in both exports and imports. Such factors as the decline in commodity prices, the consequences of the pandemic, as well as the volatility of the exchange rates of major currencies create unfavorable dynamics. In the article, the authors analyze the domestic and foreign experience of state export support. The article notes that one of the problems is the organization of marketing of export products in the region. In trade, marketing plays an almost paramount role. Domestic manufacturers should look for options for the most attractive marketing solutions and take into account the peculiarities of the consumer culture. The directions of improving the marketing of export products by the subjects of the Republic of Kazakhstan are proposed. Key words: export, foreign economic activity, export potential, strategy, state support for export, marketing of export products.